Technology adoption and socio-economic determinants of cashew farming in North Kerala - Sajeev, M.V.; Saroj, P.L.; Manjusha, A.V. Meera (Journal of Plantation Crops, 2015)
The present investigation analyses the existing technology utilization status in the Kannur and Kasaragod districts of Kerala state, as a prerequisite for developing and initiating innovative cashew production technology interventions for combating low productivity and profitability from cashew cultivation. An ‘ex-post-facto cause to effect’ design was used, and a rural appraisal ascertained that the levels of technology utilization were significantly low among cashew farmers in this region. The majority of farmers surveyed exhibited a low level of technology utilization status in cashew farming. Four socio-personal variables viz., extension contact, extension participation of cashew farmers, information and communication technologies (ICT) usage and cosmopoliteness and seven economic variables viz., farm size, area under cashew, number of yielding cashew trees, expenditure in agriculture, net income from agriculture, expenditure in cashew farming and net income from cashew farming were found to have a significant positive contribution towards adoption of cashew production technologies. Stepwise regression yielded a model with four predictors viz., number of yielding cashew trees, extension participation, net income from agriculture and farm size (negative effect) explaining up to 47.5 per cent of the variation in technology utilization among cashew farmers.